Concurrence of intraoperative hypotension, low minimum alveolar concentration, and low bispectral index is associated with postoperative death - Willingham, Mark D (Anesthesiology, 2015)
BACKGROUND: An intraoperative concurrence of mean arterial pressure <75 mmHg, minimum alveolar concentration <0.8 and bispectral index <45 has been termed a “triple low” state. An association between triple low and postoperative mortality has been reported, but was not replicated in a subsequent study. We pooled existing data from clinical trials to further evaluate the purported association in an observational study. METHODS: This retrospective observational study included 13,198 patients from three clinical trials: B-Unaware, BAG-RECALL, and Michigan Awareness Control Study. Patients with greater than 15 not necessarily consecutive minutes of triple low were propensity matched to controls with similar characteristics and comorbidities. A multivariable Cox proportional hazards model was used to evaluate the association between triple low duration and postoperative mortality. RESULTS: Thirty-day mortality was 0.8% overall, 1.9% in the triple low cohort, and 0.4% in the non-triple low cohort (Odds Ratio (OR) [95% Confidence Interval (CI)] = 5.16 [4.21 to 6.34]). After matching and adjusting for comorbidities, cumulative duration of triple low was significantly associated with an increased risk of mortality at 30 days (Hazard Ratio (HR) 1.09 [1.07 to 1.11] per 15 minutes) and 90 days (HR 1.09 [1.08 to 1.11] per 15 minutes). CONCLUSIONS: There is a weak independent association between the triple low state and postoperative mortality, and our propensity-matched analysis does not suggest that this is an epiphenomenon.